Kontaminasi Bakteri Pada Saus Tomat Mie Ayam di Pasar Condong Catur Sleman Yogyakarta Tahun 2013 - Nadifah, Fitri; Yasintha Bhoga, Maria; Prasetyaningsih, Yuliana (Jurusan Biologi UIN Alauddin Makassar, 2014)
The tomato sauce is a complementary food that is often served with other foods, such as chicken noodles. Various factors can be the cause of contamination of tomato sauce by microbes like bacteria. These factors include environmental conditions that are not clean or container that was left open. Bacterial contamination in tomato sauce can result not suitable for consumption. Given by the high public interest in the consumption of tomato sauce with chicken noodle, it is necessary to observe the bacterial contamination of chicken noodle tomato sauce. To determine the bacterial contamination in tomato sauce of chicken noodle in traditional market of Condong Catur, Sleman, Yogyakarta. The samples used were tomato sauces that are used by chicken noodle stalls in the Condong Catur traditional market. Sampling was also carried out by recording the environmental conditions stalls and tomato sauce serving. To determine the bacterial contamination, samples examined in the laboratory based on the total bacterial count method using plate count agar (PCA) media. Seven of the ten samples showed the total number of bacteria <104 CFU/ml, whereas the other three samples are not suitable for consumption by the total number of bacteria >104 CFU / ml. The main factors of high contamination is poor hygiene of chicken noodle stall environmental, tomato sauce containers that are less clean and are often left open.Keywords: tomato sauce, total bacteria